Discourse and genre - Bax, Stephen (Palgrave Macmillan, 2011)
Includes bibliographical references and index; "This accessible guide to discourse employs an innovative, inductive approach, with a clear focus on genre that allows students to examine language in context. Using real texts, students are shown how each dimension of discourse links together and are offered practical guidance on how to carry out a discourse analysis project"-- Provided by publisher